AN INVESTIGATION OF RELATIONSHIP BETWEEN THE TEACHERS’ CREATIVITY AND THE STUDENTS’ MOTIVATION IN LEARNING ENGLISH - Shofiyatul Huriyah (Universitas Islam Negeri Alauddin Makassar, 2019)
This study was the investigation of relationship between teachers’ creativity and students’ motivation in learning English. The subjects were 112 students of the Eleventh grade of vocational school, OKU. The instrument used for data collection was questionnaire. The data were statistically analyzed by using SPSS program for percentage, frequency, mean score, standard deviation, t-test and correlation coefficient. The finding from this study indicated that the teachers’ creativity was categorized good level while the result of the students’ motivation in learning English showed that 73 students got high motivation level with percentage 66.71% and 38 students gained average motivation level with percentage 33.92%. It meant that most of the students had high motivation in learning English. The correlation coefficient was 0.786 and the correlation level of significance was 0.000<0.05. Therefore, there was positive relationship between the teachers’ creativity and the students’ motivation in learning English.